(untitled) (Journal of the Bangladesh Association of Young Researchers, 2011)
Two pot experiments were conducted at the Dept. of Soil, Water and Environment, University of Dhaka to examine the effects of Zn on red amaranth (Amaranthus sp.) and rice (Oryza sativa). The soil collected from Bhaluka, Mymensingh (Chandra series), had the following general characteristics; pH 6.0, E.C 134 μS cm-1, organic matter 2.20%, organic carbon 1.27%, total N, P, K 0.024, O.07 and 0.05 % respectively. The total Zn content was 20 ppm and the texture was silty loam. Four Zn levels were maintained by treating the experimental soils with 0, 200, 300 and 400 mg Zn/kg soil. Roots & shoots of red amaranth and rice were collected after 45 and 90 days of sowing respectively. A significant impact of zinc was observed on growth and yield of red amaranth and rice. The concentration of zinc increased with increasing zinc treatment in red amaranth and rice roots, shoots and grain. The length of roots and shoots, the fresh and dry matter production decreased with increasing zinc levels for red amaranth. In case of Rice the length of roots, shoots and spikelets increased with increasing zinc levels and the highest was observed at 200 ppm Zn. The fresh and dry matter production at first decreased at 200 ppm Zn but increased at 300 and 400 ppm Zn for Rice. The results showed that zinc influenced the growth and yield of red amaranth and rice. Keywords: Zinc; Toxicity; Treatments; Yield; Uptake; Heavy metal. DOI: 10.3329/jbayr.v1i1.6836 Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.79-91